Pattern of F-18 FDG Uptake in Colon Cancer after Bacterial Cancer Therapy Using Engineered Salmonella Typhimurium: A Preliminary In Vivo Study. (19th April 2022) - Chong, Ari; Nguyen, Dinh-Huy; Kim, Hyeon Sik; Chung, June-Key; Min, Jung-Joon
Abstract : Purpose . Bacterial cancer therapy (BCT) research using engineered Salmonella typhimurium has increased in recent years. 2-Deoxy-2[ 18 F] fluoro-D-glucose positron emission tomography (FDG PET) is widely used in cancer patients to detect cancer, monitor treatment responses, and predict prognoses. The aim of this pilot study was to investigate FDG uptake patterns in a mouse tumor model after BCT. Procedures . BCT was performed via the intravenous injection of attenuated S. typhimurium (SL Δ ppGpp/lux) into female mice bearing a tumor (derived from CT26 murine colon cancer cells) in the right thigh. 18 F-FDG PET images acquired before BCT and at different time points after BCT. In vivo bioluminescence imaging confirmed bacterial presence in the tumor. The tumor volume, standardized uptake value (SUV) of FDG (SUVmax and SUVmean), early SUV reduction%, and normalized tumor volume change were analyzed. Results . Early after BCT (1 or 2 days post-injection (dpi)), FDG tumor uptake decreased in 10 out of 11 mice and then increased at later stages. FDG uptake before BCT was correlated with normalized tumor volume change after BCT. Early FDG reduction% after BCT was correlated with normalized volume change after BCT. Conclusions . Early after BCT, FDG tumor uptake decreased and then increased at later stages. The higher the FDG tumor uptake before BCT, the better the BCT response. FDG uptake patterns were related to tumor volume change after BCT. Therefore, FDG uptake was a good candidate for evaluating BCT.